Prestressed concrete: problems and solutions - Raju, N. Krishna (CBS Pub, 2015)
Prestressed concrete: problems and solutions / Raju, N. Krishna. -- New Delhi: CBS Pub., 2015 624.18342 R162e3 3rd ed. No. of Copies : 1